Application of the Forward Chaining Method in Diagnosing Tomato Fever - Edi Susanto; Gustientiedina, Gustientiedina; Siddik, Muhammad (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
Health is a factor that always needs to be taken care of by each personal. Some things you can do to stay healthy are eating nutritious foods, exercising, taking care of the environment, etc. However, a person can experience health problems due to communicable diseases and non-communicable diseases. A communicable disease is a disease that can be transmitted from one person to another, directly or indirectly. One of the infectious diseases discussed some time ago in India was tomato flu. Tomato flu is an illness that results from a red rash and blisters that look like tomatoes caused by the flu. This disease is contagious in children under five years old. Tomato flu has some symptoms that are common with other infectious diseases, so people can be infected with other infectious diseases. The role of experts is necessary, but the number of experts cannot be compared with the number of victims. Therefore, an expert system is needed to diagnose these infectious diseases by the method of Forward Chaining. This method was chosen because it can diagnose infectious diseases based on a set of established data. Expert system testing is done using Black Box Testing, where each tested item generates a succesfull state.